Cystinuria, an Atypical Presentation and Challenges of Establishing its Diagnosis in a Poor Resource Set Up - Mishra, Bijaya; Bhatta, Nisha Keshary; Pokhrel , Anupam; Lamsal, Madhab (Journal of Nepal Health Research Council, 2023)
Cystinuria is an autosomal recessive defect in re-absorptive transport of amino acids: cysteine, ornithine, arginine and lysine from renal proximal convoluted tubules leading to urinary excretion of these amino acids. The phenotypic manifestations are recurrent urolithiasis, hematuria, flank pain and frequent urinary tract infection. An eighteen years old boy, diagnosed case of cystinuria at the age of two years is presented in this case report highlighting the atypical presentation of recurrent infections with multiple organ involvement. The challenges in establishing the diagnosis and the role of simple biochemical tests in confirming the diagnosis in a poor resource setup is highlighted. Performance of simple biochemical tests in the urine sample of this patient was done for the utility of these tests for future diagnostic purpose in any suspected cases of cystinuria in our set up.Keywords: Case report; cystinuria; Nepal.